The Risk of Hypertension in Adulthood as a Consequence of Adolescent Obesity - Simbolon, Demsa; Yorita, Epti; Talib, Ruzita ABD (UI Scholars Hub, 2019)
Population increase in adolescence are associated with increased overweight and obesity problems. If this problem not early intervention will have an impact on increasing hypertension prevalence and risk of death. This research aimed to explain the consequences of overweight and obesity in adolescent to hypertension in adults. The study used Indonesian Family Life Survey (IFLS) data with a retrospective cohort study. Adolescent BMI measurements on 2007 and the risk of hypertension on 2014. Population are all adolescents aged 10-20 years in 2007. Sample of 1,697 adolescent who randomly IFLS 2007 with the inclusion criteria: biological children and a single birth, children living with biological parents, children remain alive until adulthood on 2014. Multivariate analysis used logistic regression. The study found 8.1% women and 5.6% men were overweight and obes. In adulthood, there was a 45.4% incidence of hypertension. Incidence of hypertension in men (67.3%) more than women (26.8%). The multivariate model showed adolescence BMI affects the blood pressure after controlled the BMI adult, adolescence blood pressure, area of residence, and gender.Gender interacts with adolescence BMI. The risk of hypertension in adulthood based on overweight and obese in adolescent boys is 3 times and girls is 2 times.